Atypical adult onset pityriasis rubra pilaris: a rare chronic form of pityriasis rubra pilaris - Kuvvarapu, Ajai K.; Gopal, K. V. T.; Raju, P. V. Krishnam; Rani, B. Rekha (International Journal of Research in Dermatology, 2022)
Pityriasis rubra pilaris (PRP) are a group of clinically similar papulo squamous dermatoses which present with erythematous, hyperkeratotic perifollicular papules which tend to coalesce to form plaques and may progress to erythroderma. We report a case of 46-year-old female patient who came with chief complaint of itching and burning sensation and scaly patches on extremities since one year. On dermatological examination well demarcated hyperkeratotic scaly plaques with follicular plugging and peripheral rim of erythema were seen over extensor and flexor aspects of elbows, knees, thighs, legs, dorsum of foot and gluteal region. Diffuse palmoplantar keratoderma, diffuse scaling and follicular plugging of the scalp, thickened brownish black nails were seen. On histopathology alternating layers of orthokeratosis and parakeratosis, follicular plugging with perifollicular parakeratosis, acanthosis with broad rete ridge, perivascular lymphocytic infiltration in upper dermis was seen, suggestive of PRP. Patient responded well to oral acitretin 25 mg once daily combined with oral methotrexate 10 mg once weekly along with topical emollients and corticosteroids after 6 weeks of treatment.